The Haidilao Company - McFarlan, F. Warren (Franklin Warren); Zheng, Xiaoming; Zhao, Ziqian ([London] : SAGE, 2016)
If you had to wait for two hours before you can get a table at a certain restaurant, would you still choose to dine there? Even though a long wait does not appeal to anyone, you might be surprised to find that the front lobbies of Haidilao Hot Pot restaurants are frequently filled with groups of friends and families waiting for one or two hours to dine. Why do they choose to wait here patiently while there are alternative restaurants nearby?
Originally Published in: McFarlan, F. W., Zheng, X., & Zhao, Z. (2011). The Haidilao Company. 0-711-231. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Hai Di Lao Huo Guo (Firm); Organizational change -- Case studies; Competition -- Case studies; Leadership -- Case studies; Restaurant management -- China -- Case studies